STRENGTHENING OF PROFESSIONAL NURSING CARE METHODS (MAKP) TEAM NURSING METHOD IN RSUD DR. R. KOESMA TUBAN - Tin Dwi Kartiningsih; Adhe Anniza Pramesti; Yuzita Nurfitriani; Joko Prasetyo (Media Bina Ilmiah, 2024)
Hospitals is health service organization unit by providing comprehensive health services that include promotive, preventive, curative and rehabilitative for all levels of society, often experience problems related to community dissatisfaction with the quality of hospital services which are considered unsatisfactory. Nursing service is one of the factors that determines the good and bad quality and image of the hospital. In addition to the form of service which has special characteristics, namely the implementation of continuous 24-hour service, it is also one of the most numerous health professional workers in hospital. The Professional Nursing Care Model (MAKP) which is currently becoming a trend in Indonesian nursing is the MAKP with comprehensive method of providing nursing care. MAKP is method of providing nursing care in which a professional nurse leads group of nursing staff in providing nursing care to patients through cooperative and collaborative efforts. According to an interview conducted by the residency team to one of the Heads of Room at RSUD Dr. R. Koesma, Tuban Regency, the application of MAKP uses the team method. However, in practice it is still more likely to use functional methods. After the implementation was carried out in the form of providing Socialization of MAKP Strengthening Team Methods to nurses in the Lily Room at RSUD, found the following evaluation results: The Room Nurse will apply the Team MAKP method continuously and consistently. Then, supervision will be carried out periodically so there are no more findings that result in MAKP Team's method not running optimally